A study on feeding practice and its effect on growth and morbidity of infants in the first 6 months of life in slums of Bankura Municipality - Gupta, Avisek; Tanjib Hassan Mullick; Gourab Biswas; Chakraborty, Sohanjan (Asian Journal of Medical Sciences, 2022)
Background: Infant feeding practice in first 6 months of life is a major determinant of growth, nutritional status, and morbidity. Aims and Objectives: This study conducted to assess the infant feeding practice in first 6 months of life and to determine its effect on growth, nutritional status, and morbidity of study participants. Materials and Methods: A population-based longitudinal study was conducted among 49 infants in slums of Bankura Municipality within 1 week of their birth and they were followed up to the age of 6 months. Results: Proportions of male and female infants were almost equal. Proportions of exclusively breastfed infants at 0, 3, and 6 months were 87.8%, 79.6%, and 46.9%,respectively. Mean weight and length gain at 6 months were significantly higher in infants with increased duration of exclusive breastfeeding (P=0.008 and 0.042, respectively). Mean cumulative infant feeding score (at 6 months) was higher among normal babies (115.6±0.7.3) than the underweight babies (110.0±3.7). Mean cumulative morbidity score at 6 months was lower in infants who were exclusively breastfed for 6 months (7.2±2.5) than those who were exclusively breastfed for <6 months (7.8±2.6). Mean weight gain (at 6 months) was significantly increased with higher maternal education (P=0.030). Linear regression showed that weight gain and length gain had significantly positive linear relation with cumulative infant feeding score at 6 months, whereas cumulative morbidity score had negative but not significant correlation with weight gain and significantly negative linear relation with length gain. Conclusion: This study identified that various components of infant feeding practice in study participants were suboptimal. It was also observed from this study that feeding practice was important determinant for growth, nutritional status, and morbidity.